2014
DOI: 10.1590/s1806-37132014000300014
|View full text |Cite
|
Sign up to set email alerts
|

Combined pulmonary fibrosis and emphysema: an increasingly recognized condition

Abstract: Combined pulmonary fibrosis and emphysema (CPFE) has been increasingly recognized in the literature. Patients with CPFE are usually heavy smokers or former smokers with concomitant lower lobe fibrosis and upper lobe emphysema on chest HRCT scans. They commonly present with severe breathlessness and low DLCO, despite spirometry showing relatively preserved lung volumes. Moderate to severe pulmonary arterial hypertension is common in such patients, who are also at an increased risk of developing lung cancer. Unf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
2
19
0
3
Order By: Relevance
“…22 This may delay diagnosis, as spirometry is the most easily accessible pulmonary function test. 27 Although some studies reported lower values of DLco in patients with CPFE compared to in IPF, 24 including in our study and a study by Jacob et al 28 , similar values were observed in both groups (IPF and CPFE). Interestingly, Kco was lower in the CPFE group.…”
Section: Discussionsupporting
confidence: 82%
“…22 This may delay diagnosis, as spirometry is the most easily accessible pulmonary function test. 27 Although some studies reported lower values of DLco in patients with CPFE compared to in IPF, 24 including in our study and a study by Jacob et al 28 , similar values were observed in both groups (IPF and CPFE). Interestingly, Kco was lower in the CPFE group.…”
Section: Discussionsupporting
confidence: 82%
“…This is explained by the cohabitation of the two types of lesions present in CPFE: emphysema and fibrosis. While emphysema causes hyperinflation, obstruction of airways, and greater lung compliance, fibrosis causes restrictive effects, traction to support the small airways and prevent them from collapsing, and a decrease in lung compliance 46. Therefore, CPFE patients have shown a faster decrease in forced expiratory volume in 1 second (FEV1)/forced vital capacity (FVC) than patients with IPF only, and a higher decrease in vital capacity (VC) and FVC compared to patients with COPD alone 53 , 54…”
Section: Discussionmentioning
confidence: 99%
“…HRCT scanning is an essential part for diagnosing CPFE. Anyway, the relative contributions of pathological characteristics vary among patients with CPFE [8]. Diagnosis of CPFE on HRCT is still the certain method to assess the degree of emphysema and fibrosis, which may make the progress effective and accurate [9].…”
Section: Discussionmentioning
confidence: 99%